Скінченностанова спряженість лінійних функцій на кільці цілих 2-адичних чисел - Боднарчук, Ю.В.; Морозов, Д.І. (Видавничий дім "Академперіодика" НАН України, 2008)
For automorphisms of an infinity binary tree which are realized as linear functions on the ring of integer 2-adic numbers, the problem of finite state conjugation has solved.